2019
DOI: 10.1111/jon.12642
|View full text |Cite
|
Sign up to set email alerts
|

Brain MR Spectroscopy Changes Precede Frontotemporal Lobar Degeneration Phenoconversion in Mapt Mutation Carriers

Abstract: BACKGROUND AND PURPOSE The objective of this study was to longitudinally investigate the trajectory of change in 1 H MRS measurements in asymptomatic MAPT mutation carriers who became symptomatic during follow‐up, and to determine the time at which the neurochemical alterations accelerated during disease progression. METHODS We identified eight MAPT mutations carriers who transitioned from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…An elevation in myoinositol (mI) or mI to creatine (mI/Cr) and a decrease in the neuronal integrity marker NAA or NAA/Cr have been found in symptomatic patients with FTLD (83), while only elevated mI/Cr in the posterior cingulate gyrus has been reported in asymptomatic MAPT mutation carriers (8). During longitudinal follow-up in MAPT mutation carriers who converted from the asymptomatic to symptomatic disease, serial 1 H MRS from the posterior cingulate voxel demonstrated that metabolite ratio changes, characterized by increasing mI/Cr and decreasing NAA/mI ratios, begin to accelerate ∼2 years prior to symptom onset (40).…”
Section: Proton Magnetic Resonance Spectroscopymentioning
confidence: 99%
“…An elevation in myoinositol (mI) or mI to creatine (mI/Cr) and a decrease in the neuronal integrity marker NAA or NAA/Cr have been found in symptomatic patients with FTLD (83), while only elevated mI/Cr in the posterior cingulate gyrus has been reported in asymptomatic MAPT mutation carriers (8). During longitudinal follow-up in MAPT mutation carriers who converted from the asymptomatic to symptomatic disease, serial 1 H MRS from the posterior cingulate voxel demonstrated that metabolite ratio changes, characterized by increasing mI/Cr and decreasing NAA/mI ratios, begin to accelerate ∼2 years prior to symptom onset (40).…”
Section: Proton Magnetic Resonance Spectroscopymentioning
confidence: 99%
“…Pre-symptomatic MAPT mutation carriers exhibit evidence of insidious radiological involvement, typically beginning in the medial temporal lobes, extending to the insula and accelerating 2-years before symptom onset (Rohrer et al, 2015 ; Panman et al, 2019 ; Jiskoot et al, 2019 ; Dopper et al, 2016 ; Chen et al, 2019a ). Multimodal MRI based classification models suggest that individual radiological changes may not detectable until a few years before phenoconversion (Feis et al, 2019 ; McKenna et al, 2022 ).…”
Section: C9orf72mentioning
confidence: 99%
“…MR spectroscopy studies have suggested a relatively stereotyped sequence of events, beginning with increased mI/Cr ratio (indicators of glial activity), followed by decreased NAA/mI ratio (markers of loss of neuronal integrity) and subsequent atrophy (Christidi et al, 2022 ). MRS studies of presymptomatic MAPT mutation carriers are predominantly single voxel studies focusing on different regions of interests (ROIs) such as the posterior cingulate gyrus inferior precuneus (Chen et al, 2019a ; Kantarci et al, 2010 ) or medial frontal lobe (Chen et al, 2019c ). Similar to structural findings, these radiological changes accelerate in the 2-years preceding symptom onset (Chen et al, 2019a ).…”
Section: C9orf72mentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies also reported cerebral metabolite changes in extra-motor regions. Previous studies performed in asymptomatic genetic carriers of mutations associated with FTLD using MRS-derived markers exhibit an encouraging discriminatory ability to identify patients from healthy controls; however, more data are needed to determine their ability to assist with the diagnosis in early stages and in distinguishing from disease mimics ( 232 239 ).…”
Section: Biomarkersmentioning
confidence: 99%